Re-SILAC: A Simple and Convenient Approach for the Preparation of the SILAC Internal Standards - Yu, Tianying; Yi, Tailong; Tian, Miaomiao; Xu, Zhongwei; Zhang, Yao; Zhai, Linhui; Yang, Xiaoming; Xu, Ping (Current Proteomics, 2016)
SILAC (Stable Isotope Labeling with Amino acids in Cell culture) is one of the most popular methods in quantitative proteomics field. The internal standards of SILAC can mark a variety of clinical samples or tissues instead of labeling the whole organism and play an important role in proteomics. Preparing the SILAC internal standards has been difficult and time-consuming for culturing cell lines, therefore a simple and convenient Re-SILAC method was introduced. Cell lines labeled with SILAC were thawed in SILAC medium to be remarked again. Comparing the morphology, size, growth curve and proteome of MHCC97-L between Re-SILAC and SILAC cell lines, it was found that SILAC-labeled cells that were frozen with liquid nitrogen had no influence on Re- SILAC-labeled. In conclusion, Re-SILAC method is a useful method for preparing SILAC internal standards.
Keywords: quantitative proteomics